Al Hawariyyun Dalam Perspektif Tafsir ath-Thabari Karya Abu Ja’far Muhammad bin Jarir ath-Thabari - Muhammad Saekul Mujahidin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
Isa as is a prophet sent by Allah, who is included in the category of prophet ulul azmi among other prophets. He invited his people, the Children of Israel, to worship Allah and was accompanied by his close friends, namely hawariyyun. this friend always helps preach Isa wherever he is when he is sad and happy, there are many interpretations that clarify who hawariyyun is, one of which is the interpretation of ath-thabari which says that hawariyyun is a friend of the dean Isa as. This article uses Library Research research by prioritizing in-depth analysis of various journals, books or literature related to research. The Qur'an does not provide detailed information about hawariyyun, but many interpretations explain who hawariyyun is, one of which is the interpretation of ath-thabari which says that hawariyyun is a friend of Isa's dean who always wears all white clothes, is also a laundress, and fish seekers, so that hawariyyun are the chosen people chosen by the prophet Isa to help his preaching to his people.